Recent Advances in Biosorption of Copper and Cobalt by Filamentous Fungi - Dusengemungu, Leonce; Kasali, George; Gwanama, Cousins; Ouma, Kennedy Ochieng (Frontiers in Microbiology, 2020)
Copper (Cu) and Cobalt (Co) are among the toxic heavy metals from mining and other industrial activities. Both are known to pose serious environmental concerns particularly to water resources if not properly treated. In recent years several filamentous fungal strains have been isolated, identified and assessed for their heavy metal biosorption capacity for potential application in bioremediation of Cu and Co wastes. Despite the growing interest in heavy metal removal by filamentous fungi, their exploitation faces numerous challenges such as finding suitable candidates for biosorption. Based on current findings, various strains of filamentous fungi have high metal uptake capacity, particularly for Cu and Co. Several works indicate that Trichoderma, Penicillium and Aspergillus species have higher Cu and Co biosorption capacity compared to other fungal species such as Geotrichum, Monilia and Fusarium. It is believed that far more fungal species with even higher biosorption capability are yet to be isolated. Furthermore, the application of filamentous fungi for bioremediation is considered environmentally friendly, highly effective, reliable and affordable, due to their low technology pre-requisites. In this review, we highlight the capacity of various identified filamentous fungal isolates for biosorption of copper and cobalt from various environments and their prospect.